ANALYSIS OF WASTE MATERIAL COEFFICIENT FOR CONCRETE CASTING WORK USING BIM CUBICOST TAS - ., Safri; Hermania, Tia Octaviani (POLITEKNIK NEGERI JAKARTA, 2024)
One of the construction project activities that has a large volume of work on the upper structure is casting work. In concrete requirement planning, contractors usually multiply the book by 10%. However, in practice, the concrete requirement is still less than planned. Therefore, concrete requirement planning must be calculated accurately. The volume of concrete needs to be multiplied by the waste material coefficient. This research was conducted on the XYZ Project by directly observing to obtain the volume of realized concrete purchased so that the value of the material coefficient that has taken into account waste material will be obtained. BIM Cubicost TAS is used to minimize planning volume calculation errors. The results of this study show that for horizontal casting work, the largest percentage of residual material is 3.133%, and the average percentage of residual material for horizontal casting is 2.192%. Meanwhile, for vertical casting work, the largest percentage of remaining material is 7.219% and the average percentage of remaining vertical casting material is 3.015%. Finally, the waste material coefficient is obtained as 1.022 for horizontal casting and 1.03 for vertical casting. In the AHSP Ministerial Regulation No. 1 of 2022, the coefficient value of materials for casting work using ready-mix concrete is 1.02. This reveals that the coefficient value in AHSP Minister of Public Works and Public Housing Regulation No. 1 of 2022 has not fully calculated the real waste material in the field. The analyzed coefficient values in this study can be used as a reference for the project to determine coefficients in the AHSP and aid in planning concrete volume requirements because it already takes into account the real waste material in the field.